Identity Orientations And Forms Of Social Exchange In Organizations - Flynn, Francis J. (Academy of Management Review, 2005)
I attempt to explain why employees prefer different forms of social exchange by proposing that such preferences align with their identity orientations. I also develop a model outlining how identity orientations play an important role in developing employee exchange relations and how they may help predict the consequences of exchange dynamics. By identifying linkages between identity orientations and forms of social exchange, I hope to stimulate future research on the connections between social exchange theory and the identity orientation framework.